Factors Affecting Employee Satisfaction at PT. Operational Division of Terminal-B TPK Belawan Pelindo-I Branch - Yustisar, Muhamad; Gemasih, Husna; Eliyin, Eliyin; Rayuwati, Rayuwati (Publisher Cv. Inara, 2022)
This study aims to determine whether compensation, work itself, promotion, work supervision, and co-workers partially and simultaneously have a positive and significant effect on employee job satisfaction at PT Pelindo-I branch TPK Belawan Terminal-B operational division. The data analysis technique used is the quantitative method with the help of the SPSS version 20.0 program. This research uses Confirmatory Factor Analysis and Multiple Linear Regression. The population in this study were all employees of the operational division at PT Pelindo-I branch TPK Belawan Terminal-B operational division, and a sample of 82 respondents. Primary data collection using a questionnaire. The results of the Confirmatory Factor Analysis test show that the components that most influence job satisfaction are compensation with eigenvalues of 2,644 and the work itself with eigenvalues of 1,274. The results of the study harmed job satisfaction and the work itself had a positive and significant effect on job satisfaction at PT Pelindo-I Branch TPK Belawan Terminal-B operational division. Compensation and the work itself simultaneously have a positive and significant effect on employee job satisfaction at PT Pelindo-I Branch TPK Belawan Terminal-B operational division.